Total Joint Arthroplasty of a Proximal Interphalangeal Joint with Proximal Metal Surface Replacement and Distal Hemi-Hamate Autograft: A Long-Term Follow-Up - Caroline Wu, BS; Matthew Drake, MD; Kenneth R. Means, Jr., MD (Journal of Hand Surgery Global Online, 2022)
A 28-year–old female recreational athlete presented with middle finger proximal interphalangeal joint pain, stiffness, and ulnar deviation deformity 2 years after internal fixation of a middle phalanx base fracture-dislocation. Radiographs revealed posttraumatic changes on both sides of the proximal interphalangeal joint. Having failed nonsurgical measures, she elected to proceed with surgical reconstruction. Intraoperatively, we confirmed substantial articular damage on both sides of the joint. We proceeded with hemi-hamate autograft for 80% of the middle phalanx base. We used a cobalt chrome proximal phalanx component. After healing, the patient returned to all daily-living and athletic activities with resolution of preoperative pain, stiffness, and deformity. Twelve years after surgey, she had no pain or substantial limitations because of the finger. We measured 80° of proximal interphalangeal joint motion. The grip and fingertip-pinch strength were 91% and 73%, respectively, of the contralateral dominant hand. Radiographs showed no progressive changes compared to 3 years after surgery.